Augustine and the cure of souls : revising a classical ideal - Kolbet, Paul R. (Christianity and Judaism in antiquity ;, 2010)
"Augustine and the Cure of Souls situates Augustine within the ancient philosophical tradition of using words to order emotions. Paul Kolbet uncovers a profound continuity in Augustine's thought, from his earliest pre-baptismal writings to his final acts as bishop, revealing a man deeply indebted to the Roman past and yet distinctly Christian. Rather than supplanting his classical learning, Augustine's Christianity reinvigorated precisely those elements of Roman wisdom that he believed were slipping into decadence. In particular, Kolbet addresses the manner in which Augustine not only used classical rhetorical theory to express his theological vision, but also infused it with theological content." "This book offers a fresh reading of Augustine's writings - particularly his numerous, though often neglected, sermons - and provides an illuminating point of entry into the great North African bishop's life and thought."--Jacket.